Aplikasi Berbagai Jenis Pupuk Organik Terhadap Karakter FMA Pada Rhizosfer Tebu Bud Chip - Sismita Sari; Wiwik Indrawati (Politeknik Negeri Lampung., 2019)
This study to obtain data on the number and type of FMA. Obtained amount and types of FMA in each treatment of addition of organic fertilizer dosage level. Find out whether the combination of organic fertilizer and the given organic fertilizer dose affect the amount and type of FMA. The experiment design used was Completely Randomized Design 2 Factor and 3 replications. The first factor is 4 types of organic fertilizer (P), namely: Humat acid (P) and cow manure (D), and the second factor is 4 levels of organic fertilizer dose: D0: 0%, D1: 10 tons of organic fertilizer / ha (50 g per polybag, D2: 20 ton / ha (100 g per polybag), and D3: 30 ton / ha (150 g per polybag) There were 16 experimental units and 3 total replications of 48 experimental unit plots. Myorizas were observed using binocular microscopy and digital camera, observed spores were then grouped by morphological characters including shape, color, and spore ornaments. Identification of indigenous mycorrhizae was done using manual and confirmed by using INVAM website The result of spore count on the application of organic fertilizer containing humic acid, compost fertilizer and the combination of both the highest mycorrhizae is 3,700 in the dosage of humic acid humic fertilizer 50 g + 100 g manure. 2,300 spores in organic humic acid 100 g + 100 g of fertilizer. The number of spores was moderate, ie 1,541 on humic acid fertilizer 50 g + 150 g manure, 1,323 spores at P3D3, 1,203 at treatment of P0D2, and at treatment of P2D0 mycorrhiza reached 1.096. The smallest number mycorrhizal spores of 79 spores in the dosage of manure dose 50 g. There are 4 genera of spore that found the most commonly Genus is Glomus and Acaulospora.